Experimental investigation of low-frequency sound absorption characteristics of electro-spun Polyvinylpyrrolidone (PVP) membranes. (6th April 2022) - Utkarsh,; Syed, Nabeel Ahmed; Tariq, Muhammad; Mohany, Atef; Pop-Iliev, Remon; Rizvi, Ghaus
Abstract: The sound absorption characteristics of electro-spun Polyvinylpyrrolidone (PVP) fiber-based membranes were investigated at different layer thicknesses and back cavities. The sound absorption coefficient (α) was measured utilizing the impedance tube experimental set-up conforming to ASTM 1050 and ISO10534-2. The electro-spun PVP membranes were formulated into several layering combinations viz. 2, 4, 8, 16, and 20 sheets layered together to achieve higher sound absorption in the low-medium frequency range of 100 Hz–1600 Hz. The morphological characterization of the electro-spun samples was carried out using Scanning Electron Microscope (SEM) and Digital Microscope (DM). The experimental investigation indicates that the sound absorption coefficient escalates to higher values close to one at several frequencies, increasing material thickness and back cavity. The acoustic measurements demonstrate that these electro-spun PVP fiber composites offer better noise attenuation at a significantly reduced thickness than conventional materials. These composites can have applications in industries where volume-economy is a crucial factor. Graphical abstract: Image 1 Highlights: Thickness range of electro-spun composites; 357 μm–4414 μm, with weight measurements ranging from 0.18 g to 4.37 g. High absorption coefficient (>0.9) achieved at different frequencies with increase in thickness and back cavity (0–5 cm). Highest coefficient of 0.90–0.98 achieved at lowest frequency of 537 Hz and 366 Hz with layer thickness range of 3500–4500 μm.